PERLINDUNGAN HUKUM PEMEGANG HAK DESAIN INDUSTRI BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 2000 - Cindy Wahyuni; Nuzul Rahmayani; Jasman Nazar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The development of industrial rights protection systems must be precisely adapted to the social conditions of the Indonesian people. These adjustments must be in line with Mochtar Kusumaatmadja's theory of legal development which states that good law is law that adapts to life in society itself. The purpose of establishing this industrial design law is to provide legal protection given to industrial design rights intended to stimulate the creative activity of designers to continuously create new designs. It is in the context of creating an environment capable of encouraging the spirit of creating new designs and at the same time providing legal protection that industrial design provisions are drafted. The nature of the research used is descriptive, namely research that aims to provide data that is as precise as possible about the circumstances that are the object of research. Then the problem approach used is a normative juridical approach, namely research that is only aimed at written regulations so that this writing is closely related to libraries because it will require secondary data from the library. Sources of data and legal materials used are secondary data, namely data obtained through literature studies, including books, supporting literature with the subject matter discussed and laws and regulations. The results of this study are that legal protection in the industrial design law in terms of its provisions can be seen in article 1 paragraph 5 which means that every holder of industrial design rights is a subject protected by provisions of laws and regulations. Whereas in the consideration of the judge in this case he was not too partial to the plaintiff with several legal facts that had been exposed at the trial which in fact was a place to seek justice.